Clinical peculiarities of depressive disorders in patients with malignant gastrointestinal tract tumors - N. A. Kornetov; V. A. Zhorov (Бюллетень сибирской медицины)
Unipolar depression is prevalent in inpatients with GIT tumors. Following types of depressions have been distinguished: with cognitive disturbances, anxious-hypochondriac and agitated ones. For oncologists and surgeons clinical symptoms of high likelihood of depressive disorder in oncological pathology of GIT are as follows: pain, disturbance of quality of sleep, experienced weakness and breakdown, experienced fear, tension and sudden panic with agitation.